System analysis of natural- technogenic safety elements of the largest ukrainian hydro-complexes - Бенатов, Даніель Емілович (Eastern-European Journal of Enterprise Technologies, 2015)
Issues of natural-technogenic safety (NTS) of hydro-complexes is an important component of the national security system of the country, and operative decision-making in this area is one of the major factors of sustainable development of Ukraine. At the same time, the problem of different subordination of the hydro-complex parts, inherent in Ukraine makes it difficult, and sometimes impossible to operatively estimate the real safety of the complex engineering facilities for further management decision-making. The aim of the research was to develop an effective, representative and easy to use method for multi-criteria integrated assessment of NTS problems at 18 largest Ukrainian hydro-complexes as complex natural-industrial geological-engineering systems. The expert method of pairwise comparisons in combination with the analytic hierarchy process (AHP) was used in the research. The values of the integral danger index (IDI) and priority measures to prevent threats to NTS were defined for each of the studied facilities. Also, the global priorities of factors and prevention measures for all of the studied facilities in general were identified. Expert surveys were conducted in 2003 and in 2013. The data obtained allowed to track trends and changes in estimating the situation in the area of operation of the largest Ukrainian hydro-complexes in the long retrospective.